Vitamin D deficiency and anemia risk in children: a review of emerging evidence - Uwaezuoke SN (Dove Medical Press, 2017)
Samuel N Uwaezuoke1,2 1Department of Paediatrics, College of Medicine, University of Nigeria, Nsukka, 2Department of Paediatrics, University of Nigeria Teaching Hospital, Ituku-Ozalla, Nigeria Abstract: There has been renewed scientific interest in the sequelae of vitamin D deficiency, given the emerging evidence on the diverse biologic functions of vitamin D, besides its fundamental role in bone and mineral metabolism. For the past decade, the evidence in the medical literature pointing to a relationship between anemia risk and vitamin D deficiency has been accumulating. This paper critically reviews the current evidence linking vitamin D deficiency to anemia risk in children. The synthesized evidence indicates that the studies, which were preponderantly conducted among the adult population, not only reported a bidirectional relationship between vitamin D deficiency and anemia but also showed a racial effect. In studies conducted among children, similar results were reported. Although the causal association of vitamin D deficiency with anemia risk (especially iron-deficiency anemia) remains debatable, the noncalcemic actions of the vitamin and its analogs hold prospects for several novel clinical applications. There is, however, unanimity in many reports suggesting that vitamin D deficiency is directly associated with anemia of chronic disease or inflammation. Despite the advances in unraveling the role of vitamin D in iron homeostasis, further research is still required to validate causality in the relationship between vitamin D deficiency and anemia, as well as to determine its optimal dosing, the ideal recipients for therapeutic intervention, and the preferred analogs to administer. Keywords: calcitriol deficiency, childhood anemia, iron homeostasis, causal link